Arterial Stiffness and Wave Reflection Responses Following Heavy and Moderate Load Resistance Training Protocols - Eleftherios Karanasios; Scott Hannah; Helen Ryan ‐ Stewart; James Faulkner (The Journal of Clinical Hypertension)
ABSTRACT This study compared the acute effects of resistance training (RT) between a moderate (ML) and a high loading (HL) intensity (12RM vs. 4RM, respectively), with the same intensity of effort on arterial stiffness and wave reflection in young healthy adults. Eleven healthy adults (age 36.4 ± 6.8 years) performed two RT protocols, ML and HL, in a randomized order. Both RT sessions consisted of three sets of deadlifts and three sets of bench presses, with 2 min rest between sets and exercises. Loading intensity was 12RM and 4RM for the ML and HL conditions, respectively. Measurements of pulse wave velocity (PWV) and pulse wave analysis (PWA; e.g., augmentation index) were collected at baseline, immediately post, and 15 min post‐training. ML elicited significantly greater increases in carotid‐femoral PWV (from 6.4 ± 0.3 to 7.3 ± 0.5), and augmentation index normalized to 75 bpm (from −5.1 ± 1.1) than HL (all p < 0.05). These findings demonstrate that an acute bout of RT performed to volitional failure using lower loads and higher repetitions impose a greater workload on the arterial and cardiovascular system in comparison to a RT scheme with heavier loads and lower repetitions.